THE IMPLEMENTATION OF ACADEMIC SUPERVISION IN IMPROVING THE ABILITY OF HOMEROOM TEACHERS IN PREPARING THE HYBRID LEARNING ADMINISTRATION IN SDN WONOREJO 274 SURABAYA ACADEMIC YEAR 2021/2022 - Reny Indaryati (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
The weakness of the principal's competence in supervision will affect the quality of the school. This is aggravated with the condition of teachers who do not prepare the learning implementation plan due to an action of some teachers who ask school operators to create the lesson plan. Researchers obtained this information according to an initial interview with some principals. In addition, the principal also did not conduct coaching because he or she felt inferior to the senior teachers.Based on the aforementioned problems, it is important to acknowledge academic supervision by the principal in the case of the development of lesson plan preparation in SDN Wonorejo 274 Surabaya to improve and coach teachers in the teaching and learning process. This is at stake to improve the quality and student achievement in upgrading the quality of the school